Evaluation Factors That Determine the Dividend Payout Ratio of Commercial Banks in Nigeria - Onyeka, Virginia Nnenna (International Journal of Accounting and Financial Reporting, 2022)
The study examined the evaluation of factors that determine the dividend payout rate of commercial banks in Nigeria. The research adopted ex post facto research covering the period 2009 to 2018. Secondary data were extracted from annual reports and accounts of selected banks listed on the Stock Exchange (NSE). The data were analyzed using multiple regression techniques. Findings depict that earnings per share have a positive and nonsignificant effect on the dividend payout ratio of commercial banks in Nigeria. Retained earnings on the other hand have a negative and significant effect on the dividend payout ratio of commercial banks in Nigeria. Net profit margin and debt-equity ratio have a negative and insignificant effect on the dividend payout ratio of commercial banks in Nigeria. However, bank age has a positive and significant effect on the dividend payout ratio of commercial banks in Nigeria. The adjusted R-squared revealed that 21% of the variations in dividend payout ratio could be explained by the explanatory variables while 79% could be explained by other factors that are capable of influencing dividend payout ratio that was not studied. The implication of the findings is that only retained earnings and bank age can be used in predicting movement in the dividend payout ratio of banks in Nigeria.